Empirical Exploration of the Drivers of Human Development in Central and West Asian Countries: How Effective Are Control of Corruption, Political Stability and the Rule of Law? - Celik, Ali; Kostekci, Ahmet (Wiley, 2025)
Good governance indicators such as controlling corruption, establishing the rule of law, and ensuring political stability are central to social well-being as they affect both sustainable income growth and non-income indicators of human development. However, human development is still not a priority in Central and West Asia, where humanitarian problems are widespread and the literature on the impact of good governance on human development is limited. Moreover, the effects of corruption, rule of law and political stability on human development in Central and West Asia are not conclusive due to the limitations of inclusive studies. Therefore, this research explores the impact of economic, demographic, and environmental factors as well as governance factors such as corruption, political stability, and the rule of law on human development in Central and West Asian countries applying the advanced panel econometric techniques for the period between 2002 and 2021. The findings indicate that corruption has a negative influence on human development, but raising control of corruption has positive impact on human development. Furthermore, political stability and the rule of law positively contribute human development. Moreover, trade openness, and CO2 emissions promote human development, while inflation, unemployment and, population growth have negative effects on human development. In conclusion, the findings obtained from the study provide important clues and new perspectives for policy makers to achieve the human development goal in the region in question. Accordingly, our results stress that Central and West Asian countries need to adopt transparency and accountability-oriented policies to reduce corruption, establish the rule of law and ensure political stability in order to achieve high human development.
Keywords: central and west Asian countries; corruption; human development; political stability; rule of law